2004
DOI: 10.1523/jneurosci.4649-03.2004
|View full text |Cite
|
Sign up to set email alerts
|

Discovering Spike Patterns in Neuronal Responses

Abstract: When a cortical neuron is repeatedly injected with the same fluctuating current stimulus (frozen noise) the timing of the spikes is highly precise from trial to trial and the spike pattern appears to be unique. We show here that the same repeated stimulus can produce more than one reliable temporal pattern of spikes. A new method is introduced to find these patterns in raw multitrial data and is tested on surrogate data sets. Using it, multiple coexisting spike patterns were discovered in pyramidal cells recor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
153
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 162 publications
(158 citation statements)
references
References 69 publications
(95 reference statements)
5
153
0
Order By: Relevance
“…3g). Across the two trials the neuron will thus produce distinct spike patterns 18,26 , as observed in vitro 19,23 . When there is a prolonged period without spiking on both trials, the voltage trajectories will converge back and the same spike pattern will be obtained.…”
mentioning
confidence: 84%
See 4 more Smart Citations
“…3g). Across the two trials the neuron will thus produce distinct spike patterns 18,26 , as observed in vitro 19,23 . When there is a prolonged period without spiking on both trials, the voltage trajectories will converge back and the same spike pattern will be obtained.…”
mentioning
confidence: 84%
“…If stimulus-related information is to be coded in the precise spike times, the interaction illustrated in part c is innocuous but the one in part d is harmful. Experimental recordings of TC neurons indicate the presence of spike patterns 18,43 , which suggests that there are synchronous spike volleys at the population level. The spike volleys could be synchronous to a few SSCs (yellow highlight) or they could be synchronous across inputs to a large group of SSCs (red highlight).…”
Section: Feedforward Informationmentioning
confidence: 98%
See 3 more Smart Citations